Health and social care interventions which promote social participation for adults with learning disabilities: a review. (9th July 2014) - Howarth, Sharon; Morris, David; Newlin, Meredith; Webber, Martin
Abstract : Accessible summary: People with learning disabilities have fewer friends than others; Social care interventions are needed to help people to be more socially active in their community; This review looks at what research has already been done in this area; This is important to people with learning disabilities as it highlights the importance of having friends in, and outside of, services. Summary: People with learning disabilities are among the most socially excluded in society. There is a significant gap in research evidence showing how health and social care workers can intervene to improve the social participation of adults with learning disabilities. A systematic review and modified narrative synthesis was used to appraise the quality and outcomes of published studies in this area. Six of eleven included studies showed a positive effect on social participation. Interventions included person‐centred planning, alteration of activity patterns, a befriending scheme and skill‐based group sessions. The majority of studies were found to have a moderate risk of bias. Further evidence about the effectiveness of interventions is required to inform policy and practice.